Activity of endophytic fungi in enantioselective biotransformation of chiral amines: New approach for solid-state fermentation. (March 2023) - Pinheiro, Larissa Zambe; da Silva, Fellipe Francisco; Queiroz, Maria Sandra Ramos; Aguieiras, Erika Cristina Gonçalves; Cipolatti, Eliane Pereira; da Silva, Aline Souza; Bassut, Jonathan; Seldin, Lucy; Guimarães, Denise Oliveira; Freire, Denise Maria Guimarães; de Souza, Rodrigo Octávio Mendonça Alves; Leal, Ivana Correa Ramos
Abstract: Oranges are among the most consumed fruits in Brazil, with over 80 million tons production per year. Currently, one of the main uses of orange residues is to supplement animal feeds. However, orange residues can be used in other ways, including for obtaining enzymes. However, for the pyridoxal 5-phosphate (PLP)-dependent enzyme group, which catalyze transamination reactions, no work has been described. The use of orange-peel residues for solid-state fermentation using endophytic microorganisms is a new and interesting approach to produce these enzymes at lower cost compared to the use of purified enzymes associated to PLP co-factor. In the batch process developed in this study, it was possible to achieve a maximum conversion of 49% after 48 h of incubation, an enantiomeric excess of 99% ( R )-1, 2, 3, 4-tetra-hydro-1-naphthylamine, and productivity of 0.0102 mg biocatalyst.h −1, using the solid enzyme preparation from Alternaria arborescens as biocatalyst . In a continuous-flow system, 51% conversion and >99% ee of ( R )-1, 2, 3, 4-tetra-hydro-1-naphthylamine were achieved, with a six-fold increase productivity (0.0625 mg biocatalyst.h −1 ). We have screened different fungi samples for transaminase activity and we found a hit for solid-state fermentation. The endophytic fungus genetically identified as Alternaria arborescens showed promising results for the transaminase activity on the kinetic resolution of chiral amine blocks. Therefore, along with other improvement of the biocatalytic toolbox for chiral amines synthesis, we have found that the solid enzymatic preparation of the endophytic fungus Alternaria arborescens could accept bulky substrates with reasonable activity, compared to the wild-type transaminase already published over literature, and, with high enantioselectivity. Graphical abstract: Image 1 Highlights: First report of transaminase activity for whole cells and solid enzyme preparation of Alternaria arborescens and Sordaria sp. Higher ω-transaminase activity on solid enzymatic preparation of A. arborescens . High conversions in ( R )-1, 2, 3, 4-tetra-hydro-1-naphthylamine with solid enzyme preparation in a continuous-flow system.